Cases in educational administration - Macatangay, Josefina A. 1948- (1978)
Case Nos. 1 and 2, " The UP College of Arts and Sciences" present the need to reorganize and the tendency of some departments to backslide to practices prior to reorganization. Case No.3, "St. Mark's School" outlines a Catholic school director's dilemma in implementeng the school's admission policy. Case No. 4, "Mass Resignation", illustrates the consequences of poor human relations between an administrator and his subordinates.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: School management and organization -- Case studies. -- Philippines -- Manila metropolitan area; Universities and colleges -- Administration -- Case studies. -- Philippines -- Manila metropolitan area